Learning About Oneself from the Public Records: Editing the Report of a Research Project for the Fulton Committee - Chapman, Richard A. (Public policy and administration, 2003)
This article combines an academic study of official documents, only recently available, with the recollections and reflections of a key player in the subject studied. It therefore has a rare (perhaps unique?) approach. It reveals details of civil service attitudes towards research in the social sciences at the time of the Fulton Committee on the Civil Service (1966-68) – important for understanding British public administration not only in the 1960s but also up to the present time. It also raises significant questions about the role(s) of advisers to committees and commissions and, in particular, the work of secretaries to such bodies.